Marine heatwave intensity and duration negatively affect growth in young sporophytes of the giant kelp Macrocystis pyrifera - Bunting, Imogen; Kok, Yun Yi; Krieger, Erik C.; Bury, Sarah J.; D’Archino, Roberta; Cornwall, Christopher E. (Frontiers in Marine Science, 2024)
Kelp forests are productive and biodiverse ecosystems with high ecological, cultural, and economic importance. However, the high sensitivity of kelp to water temperature means that these ecosystems are vulnerable to marine heatwaves (MHWs), especially at the equatorward edge of their range. To date, few laboratory studies have compared the effects of MHWs of different durations or intensities on kelp, and it is difficult to determine these effects from naturally occurring MHWs in the field. We exposed juvenile sporophytes of the giant kelp Macrocystis pyrifera from Wellington, Aotearoa New Zealand to simulated MHWs three or six weeks in duration, at temperatures of 18°C, 20°C, and 22°C, corresponding to 2, 4, and 6°C above local mean summer temperatures. While all MHW treatments reduced mean kelp growth rates by over 30% relative to 16°C controls, the 22°C treatments had much more severe and wide-ranging effects, including rapid blade erosion, reduced chlorophyll fluorescence, tissue bleaching, increased δ13C values, and mortality. Nonetheless, sporophytes had some ability to recover from heat stress; within the 18°C treatment, mean relative growth rates neared or exceeded those within the control treatment within three weeks after MHWs concluded. These results support the findings of previous studies which indicate that M. pyrifera sporophytes experience a key physiological tipping point around 20°C. Additionally, our findings suggest that juvenile M. pyrifera from the Wellington population could be relatively resilient to MHWs if temperatures remain at sub-lethal levels. However, if average MHW intensities and durations continue to increase over time, survival and recruitment of juvenile kelp could be adversely affected, thus threatening the long-term persistence of giant kelp forests near the warm edge of their range in New Zealand.